Synthesis and enhanced CO2/CH4 selectivity of hyperbranched copolyimide membranes. (August 2021) - Yang, Tao; Pang, Hongchang; Chen, Zan; Duan, Cuijia; Yuan, Biao; Yan, Shuo
A series of hyperbranched copolyimides (co-HBPIs), as the completely symmetrical tetraamine monomer successfully incorporated into the linear polyimide 6FDA-ODA, were synthesized under the chemical imidization after the gel formation was avoided, as to more effectively separate CO2 /CH4 . CO2 /CH4 selectivity (74%) was observed to be improved significantly under 7‰ tetraamine contents at 2 bar and 35°C; thus, the acceptable CO2 permeability was maintained compared with the pure membrane, exceeding the 1991 upper bound. Moreover, the as-prepared membrane with 6FDA-ODA-7‰ was reported to exhibit higher CO2 /CH4 selectivity (109.14) at 10 bar and 35°C. Accordingly, the hyperbranched copolyimides will be promising candidates as membrane materials for the further separation of CO2 /CH4 gas pair.